Papillary renal cell carcinoma within a renal oncocytoma: Case report of very rare coexistence - Özer, Cevahir; Gören, Mehmet Resit; Egilmez, Tulga; Bal, Nebil (Canadian Urological Association Journal, 2014)
Renal oncocytomas accounts for 3% to 9% of primary renal neoplasms. The coexistence of renal cell carcinoma (RCC) within the oncocytoma is extremely rare. We report the case of an asymptomatic 74-year-old man with papillary RCC within oncocytoma managed with left radical nephrectomy.